Synthesis of titanium carbide (TiC) using recycled precursor for potential scale-up of low-cost MXene - M.A. Zaed; R. Saidur; K.H. Tan; Jayesh Cherusseri; A.K. Pandey; N. Abdullah; Nurul Atiqah Izzati Md Ishak (Open Ceramics, 2024)
In this study, we report the low-cost synthesis of titanium carbide (TiC) from recycled precursors and further used to synthesize MAX phase material, Ti3AlC2. The recycled precursor, carbon extracted from the used tyres using a few processes is used to synthesize TiC with high purity. The use of tyre-derived carbon offers several environmental benefits such as facile synthesis, low cost, environment-friendly, etc. The as-synthesized TiC is further used as a precursor to synthesize low-cost Ti3AlC2. The structure of TiC and Ti3AlC2 are characterized by UV–visible spectroscopy and X-ray diffraction analysis. The microstructure and surface morphology of the samples are examined using scanning electron microscope imaging and energy-dispersive X-ray spectroscopy. The chemical bonding information is analyzed by Fourier transform infrared spectroscopy and the thermal behaviour of the samples are examined using thermogravimetric analysis. The successful cost-effective synthesis of TiC and Ti3AlC2 are confirmed from XRD analysis and the samples show high purity. TiC and Ti3AlC2 show excellent thermal stability which helps in their potential applications in the future. This study proclaims a new strategy to synthesize low-cost Ti3AlC2 MXene for the large-scale production using TiC precursor where the TiC precursor is synthesized using carbon precursor.